Efficient hydrogenolysis of woody plant lignin into phenolic compounds over a CuO/CeO2 catalyst - Xu, Qian; Xiao, Ling-Ping; Wang, Qiang; Zhang, Li-Long; Sun, Run-Cang (Journal of catalysis, 2024)
[Display omitted] •The CuO/CeO2 catalyst displayed high reactivity toward RCD of woody sawdust.•The acidic and basic sites of the catalyst favor lignin depolymerization.•Selective C − O bonds scission at a mild condition led to high yields of monophenols.•Synergistic effects of hydrogen and catalyst assisted the cleavage of C − O linkages. Hydrogenolysis of lignocellulose into renewable phenolic monomers through the reductive catalytic degradation (RCD) strategy is limited by cost and applicability, and there is a need to develop effective catalysts with controlled cost and greater applicability. Herein, we report the fabrication of CuO/CeO2 catalyst toward RCD of lignocellulose for the production of monomeric phenols with different side chains. The catalyst can be adapted to softwoods (Larch and Pinus) and hardwoods (Eucalyptus and Poplar) with yields ranging from 8.8 % to 31.4 %, which afford certain monomer yields while controlling costs. Experimental results demonstrate that the acidic and basic sites of the CuO/CeO2 catalyst assist the metal sites in the depolymerization of lignin. Notably, the mechanistic investigation reveal that the methoxylation process occurs on the aliphatic hydroxyl group. Moreover, the synergistic effects of hydrogen and catalyst exhibit high hydrogenolysis activity, which contributes to the efficient C − O bond scission, thus generating the target monomer products.